If $\cos 3\theta = \alpha \cos \theta + \beta {\cos ^3}\theta ,$ then $(\alpha ,\beta ) = $
$(3,\,4)$
$(4,\,3)$
$( - 3,\,4)$
$(3,\, - 4)$
$\tan 3A - \tan 2A - \tan A = $
If $\theta $ is an acute angle and $\sin \frac{\theta }{2} = \sqrt {\frac{{x - 1}}{{2x}}} $, then $\tan \theta $ is equal to
$\frac{{\cos 12^\circ - \sin 12^\circ }}{{\cos 12^\circ + \sin 12^\circ }} + \frac{{\sin 147^\circ }}{{\cos 147^\circ }} = $
If $\sin 6\theta = 32{\cos ^5}\theta \sin \theta - 32{\cos ^3}\theta \sin \theta + 3x,$ then $x = $
$\tan 5x\tan 3x\tan 2x = $